Bruton’s tyrosine kinase inhibition attenuates disease progression by reducing renal immune cell invasion in mice with hemolytic-uremic syndrome - Kröller, Sarah; Wissuwa, Bianka; Dennhardt, Sophie; Krieg, Nadine; Thiemermann, Christoph; Daniel, Christoph; Amann, Kerstin; Gunzer, Florian; Coldewey, Sina M. (Frontiers in Immunology, 2023)
Hemolytic-uremic syndrome (HUS) can occur as a complication of an infection with Shiga-toxin (Stx)-producing Escherichia coli. Patients typically present with acute kidney injury, microangiopathic hemolytic anemia and thrombocytopenia. There is evidence that Stx-induced renal damage propagates a pro-inflammatory response. To date, therapy is limited to organ-supportive strategies. Bruton’s tyrosine kinase (BTK) plays a pivotal role in recruitment and function of immune cells and its inhibition was recently shown to improve renal function in experimental sepsis and lupus nephritis. We hypothesized that attenuating the evoked immune response by BTK-inhibitors (BTKi) ameliorates outcome in HUS. We investigated the effect of daily oral administration of the BTKi ibrutinib (30 mg/kg) and acalabrutinib (3 mg/kg) in mice with Stx-induced HUS at day 7. After BTKi administration, we observed attenuates disease progression in HUS mice. These findings were associated with less BTK and downstream phospholipase-C-gamma-2 activation in the spleen and, subsequently, a reduced renal invasion of BTK-positive cells including neutrophils. Only ibrutinib treatment diminished renal invasion of macrophages, improved acute kidney injury and dysfunction (plasma levels of NGAL and urea) and reduced hemolysis (plasma levels of bilirubin and LDH activity). In conclusion, we report here for the first time that BTK inhibition attenuates the course of disease in murine HUS. We suggest that the observed reduction of renal immune cell invasion contributes – at least in part – to this effect. Further translational studies are needed to evaluate BTK as a potential target for HUS therapy to overcome currently limited treatment options.